1H NMR and SPME-GC/MS study of hydrolysis, oxidation and other reactions occurring during in vitro digestion of non-oxidized and oxidized sunflower oil. Formation of hydroxy-octadecadienoates. (January 2017) - Nieva-Echevarría, Bárbara; Goicoechea, Encarnación; Manzanos, María J.; Guillén, María D.
Abstract: Both fresh and slightly oxidized sunflower oils, as models of omega-6 rich lipids, were submitted to in vitro gastrointestinal digestion and studied by 1 H NMR and SPME-GC/MS. Changes in lipolysis degree, lipid composition and oxidative level were studied by 1 H NMR. Three quantitative approaches were used and several equations were newly developed. In oxidized oil digestates slightly lower hydrolysis and a higher advance of oxidation took place during digestion. This latter was evidenced by a greater decrease of lipid unsaturation degree and enhanced generation of oxidation products ( cis, trans -hydroperoxy-octadecadienoates, cis, trans - and trans, trans -hydroxy-octadecadienoates). For the first time, the generation of hydroxy-octadecadienoates during in vitro digestion is reported. Furthermore, SPME-GC/MS study of non-digested and digested samples headspaces confirmed that lipid oxidation occurred: abundances of volatile markers increased (including potentially toxic alpha, beta -unsaturated aldehydes), especially in oxidized oils digestates. Markers of Maillard-type and esterification reactions were also detected in the digestates. Graphical abstract: Highlights: Non-oxidized and slightly oxidized sunflower oils were in vitro digested. The ongoing chemical reactions were investigated by 1 H NMR and SPME-GC/MS Oil initial oxidation level affected the hydrolysis and oxidation extent reached. The formation of hydroperoxy- and hydroxy-octadecadienoates was evidenced. Other reactions like Maillard and esterification also took place.